Penggunaan Project-Based Learning (PBL) Eco-Enzim untuk Mengembangkan Kemampuan Menyimak dan Bicara Anak - Catheriena Rosmauli Silitonga; Debie Susanti (Universitas Cokroaminoto Palopo, 2023)
This study aims to determine the effectiveness of the effect of learning the Problem Based Learning (PBL) model through Eco enzyme activities on the ability to listen and express language or speak in early childhood. This can be seen from various previous research results that the listening and speaking abilities of early childhood have not developed optimally. The learning which is assumed as an effort to improve listening and speaking skills for early childhood is by using the Problem Based Learning (PBL) learning model through Eco Enzim activities. This study used quantitative data collection techniques. The design used in this study is the Post test Only Control Design. The two groups were randomly selected and both groups were treated with PBL treatment. The post test was carried out on the experimental and control groups which arepreviously using solvin calculations. The results of the samples tested were 54 samples randomly. In the Kolmogrov-Smirnov normality test the speaking group obtained a result of 0.2, the listening group obtained a result of 0.054. In the Shapiro-Wilk normality test the speaking group obtained a result of 0.177, and the listening group obtained a result of 0.12. Then a homogeneous test was carried out with the Levene test, the result was 0.88, and in the independent sample t test, the result was 0.035, it can be concluded that HO was rejected and Ha was accepted. Therefore, there is an increase in the listening and speaking abilities of children in age group B in DKI Jakarta for the 2022-2023 school year on the effect of the eco enzyme project-based learning model. These results were obtained from data management of 118 children, through the solvin method the results obtained were 54 samples taken randomly. There is a standard deviation result looking at the distribution of data to the average, the result is 11,295 in the speaking variable, 7,808 in the listening variable. Thus that there is a significant (significant) difference between the average student learning outcomes in the listening group and the speaking group and the speaking group's results are superior to the listening group.